(untitled) (Journal of Asian Development Studies, 2015)
Television is most widespread medium of communication, having various implications in society. Nature of impact may be viewed positive or negative, that all depends on TV content. Purpose of this research study is to analyze its positive role in society, in the awareness of women rights among women. Dominant religion in District Naushahro Feroze is Islam; Islam is that religion which assures all kinds of rights to women. Not only religion but state also guarantees political, socio-cultural, economic and political rights to women. In spite of that women have been most sufferers and deprived of all kinds of rights. Development of women folk depends on their education, economic independency, political and social awareness and says in decision making. That is only possible when they would be aware of their rights. TV can play vital role in the empowerment of women by informing and educating them. This research has confirmed the impact of watching television on awareness of women rights.